2014
DOI: 10.3136/fstr.20.459
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Rebaudioside A on Microbial Diversity in Mouse Intestine

Abstract: Rebaudioside A (RA), a natural high potency sweetener, is isolated from the leaves of the Stevia rebaudiana plant, and has potential for wide use in our diet today. To investigate the effect of RA on the changes of microbial diversity in animal intestinal tract, the viable cell count and denaturing gradient gel electrophoresis (DGGE) method were used to monitor the microbial number and species in vivo, and before that, we also evaluated its influence on the growth of some selected bacteria in vitro. Our result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
26
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 35 publications
(30 reference statements)
6
26
1
Order By: Relevance
“…In the study conducted by Li et al , in 2014 [53], they evaluated the in vitro effect of Rebaudioside A on bacterial growth and observed that Rebaudioside A can inhibit the growth of S. Aureus and stimulate the growth of L. plantarum . These results indicate that Rebaudioside A can inhibit the growth of pathogenic microorganisms and stimulate the growth of probiotic microorganisms.…”
Section: Discussionmentioning
confidence: 99%
“…In the study conducted by Li et al , in 2014 [53], they evaluated the in vitro effect of Rebaudioside A on bacterial growth and observed that Rebaudioside A can inhibit the growth of S. Aureus and stimulate the growth of L. plantarum . These results indicate that Rebaudioside A can inhibit the growth of pathogenic microorganisms and stimulate the growth of probiotic microorganisms.…”
Section: Discussionmentioning
confidence: 99%
“…Rebaudioside A showed little or no effect on the growth of Escherichia coli O157 H7, Salmonella typhimurium, Listeria monocytogenes, and Bifidobacterium longum, although it could promote the growth of Lactobacillus plantarum and inhibit Staphylococcus in vitro; also, rebaudioside A posed little pressure on the composition of total bacteria, enterobacteria, and lactobacilli in vivo, suggesting that it is safe for gut microbes (Li et al, 2014). Kumari and Chandra (2015) found that S. reubaudiana secondary metabolites also had in vitro antimicrobial activity against other bacteria, including Bacillus subtilis, Staphylococcus aureus, Pseudomonas fluorescence, and E. coli (Kumari & Chandra, 2015).…”
Section: Antimicrobial Antiviral and Antibiofilm Activitymentioning
confidence: 99%
“…Rebaudioside A showed little or no effect on the growth of Escherichia coli O157 H7, Salmonella typhimurium , Listeria monocytogenes , and Bifidobacterium longum , although it could promote the growth of Lactobacillus plantarum and inhibit Staphylococcus in vitro; also, rebaudioside A posed little pressure on the composition of total bacteria, enterobacteria, and lactobacilli in vivo, suggesting that it is safe for gut microbes (Li et al, ).…”
Section: Pharmacokinetics Pharmacodynamics and Toxicologymentioning
confidence: 99%
“…In addition to the different biological fates of the LCS, there are other factors that may influence differences in LCS effects on the gut microbiotathat make it difficult to interpret outcomes. Many animal studies use LCS in amounts in excess of the ADI [137,143,144,145], rendering extrapolations of findings to humans questionable. While animal studies typically use a controlled diet with LCS consumption, the human studies mentioned above did not control diet.…”
Section: Microbiotamentioning
confidence: 99%